Penerapan Business Continuity pada Bank Central Asia - Keefe Darius Chandra (Center for Economic Studies Universitas Katolik Parahyangan, 2017)
Banks are financial institutions that have a major impact on the economic system and can affect people's lives. Hence, regulators concerned in organizing business continuity of the banking industries. PT. Bank Central Asia, Tbk. (BCA) represents businesses in the banking sector that can not escape from the natural and man threats which can interfere the bank's business. This case study presents a glimpse of how the business continuity run in BCA. Moreover, business continuity in banking can not be generalized because each bank has a different strategy. Some disasters have been handled properly for their business continuity plan in BCA are catastrophic floods that hit Jakarta in 2013 and fires at several branch offices of BCA. BCA awares of the business continuity planning as an endless process that need to be refined over time. This case study described the roadmap to the awareness of business continuity planning in BCA and how the business continuity planning methodology is run in BCA.Keyword: business continuity, bank risk